Aplikasi Pembelajaran Unified Modeling Language Berbasis Computer Assisted Instruction - Hasdiana Hasdiana; Hasanul Fahmi (Query: Journal of Information Systems, 2018)
Unified Modeling Language (UML) is one of the important materials in the analysis and design of information systems. UML is used in designing or modeling the system. UML has some form of diagram that is grouped in several aspects based on a different view. Forms of the diagram are illustrated by different functions and notations. This makes UML difficult to understand considering that time in the classroom is very limited. Therefore, it is necessary to design a learning aid based Computer Assisted Instruction (CAI). Interactive application interface helps students understand the learning materials. Students can learn independently wherever and whenever they need. The results of this study can be utilized for the development of teaching materials, especially about modeling the system with UML. Keywords: Learning, Computer Assisted Instruction, Unified Modeling Language